2010
DOI: 10.1007/s12562-009-0208-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of prostaglandin E2 in polychaete Perinereis sp. and its effect on Penaeus monodon oocyte development in vitro

Abstract: Prostaglandins are involved in the reproductive processes in a variety of animals, including crustaceans. It was found that polychaetes, the best maturation diet for shrimp broodstock, possessed the greatest variation of prostaglandin E 2 (PGE 2 ) when compared with other live feeds. The level of PGE 2 varied according to sizes, feed intake, sources and type of polychaete. The matured and also larger sand polychaete Perinereis sp. contained higher PGE 2 levels than younger and smaller sand polychaetes (18.16 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 28 publications
(32 reference statements)
1
37
1
2
Order By: Relevance
“…In addition, they have been found to contain several substances that directly stimulate the endocrine system in penaeid shrimp (e.g. steroids: Laufer et al 1997;prostaglandin: Croz et al 1988;Poltana et al 2005;Meunpol et al 2010;progesterone: Meunpol et al 2007). These combined factors demonstrate the importance of reliable, biosecure polychaete supplies for future developments in the marine shrimp (and fish) farming industry.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they have been found to contain several substances that directly stimulate the endocrine system in penaeid shrimp (e.g. steroids: Laufer et al 1997;prostaglandin: Croz et al 1988;Poltana et al 2005;Meunpol et al 2010;progesterone: Meunpol et al 2007). These combined factors demonstrate the importance of reliable, biosecure polychaete supplies for future developments in the marine shrimp (and fish) farming industry.…”
Section: à2mentioning
confidence: 99%
“…For example, ARA was found here in P. helleri at relatively high levels. It is involved in the synthesis of prostaglandins which have a broad set of physiological roles including the regulation of reproduction in crustaceans (Harrison 1990;Wouters et al 2001;Meunpol et al 2010). Several polychaetes including some from this genus (Perinereis) have been shown to contain these and other hormones that stimulate ovarian development in one of the more difficult penaeid species to breed, P. monodon (e.g.…”
mentioning
confidence: 99%
“…Penggunaan tepung cacing laut (Polychaeta) dalam pakan dapat meningkatkan jumlah induk betina yang matang gonad diduga karena kandungan hormonnya seperti hormon osmoregulasi (Andreis, 2001), hormon oxytocin/vasopressin (Oumi et al, 1996dan Fujino et al, 1999, hormon reproduksi (Meunpol et al, 2010), hormon kelamin/sex hormone (Hardege et al, 1994) dan feromon kelamin/sex pheromone (Zeeck et al, 1998). Meskipun sejumlah hormon yang berhubungan dengan reproduksi telah diindentifikasi dalam cacing laut, penggunaan cacing laut tersebut ternyata belum cukup menstimulasi terjadinya perkawinan alami pada induk udang windu asal tambak (Laining et al, 2013b).…”
Section: Pendahuluanunclassified
“…Prostanoids derived from ARA (i.e. series II prostaglandin) have significant roles in the onset of maturation, stimulation and sequestration of egg yolk and development of essential cellular machinery such as cortical rods in P. monodon (Wouters et al, 2001a, Meunpol et al, 2010, Wimuttisuk et al, 2013. It has previously been reported that the ARA:EPA ratio in mature ovaries of wild P. monodon range from 0.3-0.6 (Crocos, 1997, Marsden et al, 1991, D'Souza and Kelly, 2000, Wouters et al, 2001a, Huang et al, 2008, whilst the diet used by Coman et al (2011) contained a ARA:EPA ratio of 0.5 and resulted in a ratio of 0.57 in spawned eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Modified from Wimuttisuk et al (2013) PGF2α in the Florida crayfish Procambarus paeninsulanus (Spaziani et al, 1995, Spaziani et al, 1993, Kuruma shrimp Marsupenaeus japonicus (Tahara and Yano, 2004), and P. monodon (Wimuttisuk et al, 2013), whilst only PGE2 has been reported in the shore crab Carcinus maenas (Hampson et al, 1992) and acorn barnacle Balanus Amphitrite (Knight et al, 2000). In P. monodon, PGF2 acts as a regulator of maturation (Wimuttisuk et al, 2013), whilst PGE2 promotes the development of yolk globules and cortical rods in P. monodon oocytes during early, and late stage development respectively (Meunpol et al, 2010).…”
Section: Introductionmentioning
confidence: 99%